2016
DOI: 10.3389/fpls.2015.01243
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Affect Biomass Accumulation and Photosynthesis in Arabidopsis

Abstract: Dramatic increase in the use of nanoparticles (NPs) in a variety of applications greatly increased the likelihood of the release of NPs into the environment. Zinc oxide nanoparticles (ZnO NPs) are among the most commonly used NPs, and it has been shown that ZnO NPs were harmful to several different plants. We report here the effects of ZnO NPs exposure on biomass accumulation and photosynthesis in Arabidopsis. We found that 200 and 300 mg/L ZnO NPs treatments reduced Arabidopsis growth by ∼20 and 80%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
107
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(130 citation statements)
references
References 53 publications
(66 reference statements)
14
107
1
1
Order By: Relevance
“…Nanomaterials have been reported to improve the germination rate of rice seeds; increase the root growth of corn, tomato and cucumber; enhance the growth rate of coriander and garlic plants; protect the photosynthesis system; and aid in defense against plant disease [4,5]. However, research has also indicated that nanomaterial treatments can result in decreased germination rates and photosynthetic efficiency, reduced root and shoot length, reduction of biomass, and reduced nutrient contents in soybean [6,7]. The regulation of nanomaterials in plants is complex and dynamic and and depends on the type of nanoparticle, treatments (concentration, tduration and method), and phytohormone balance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials have been reported to improve the germination rate of rice seeds; increase the root growth of corn, tomato and cucumber; enhance the growth rate of coriander and garlic plants; protect the photosynthesis system; and aid in defense against plant disease [4,5]. However, research has also indicated that nanomaterial treatments can result in decreased germination rates and photosynthetic efficiency, reduced root and shoot length, reduction of biomass, and reduced nutrient contents in soybean [6,7]. The regulation of nanomaterials in plants is complex and dynamic and and depends on the type of nanoparticle, treatments (concentration, tduration and method), and phytohormone balance [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps due to direct interaction of TiO 2 nanoparticles with carotenoid biomolecules. However, Wang et al (2016) pointed out that genes are mainly responsible for enhancement of pigments under influence of ZnO and TiO 2 nanoparticles.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…The randomly selected 10 plants after 14 days were washed with distilled water, blotter dried and fresh weight was determined. Dry weight was determined after drying the plant material in oven at 70 0 C for 24h and recorded 23 .…”
Section: Biomass Studymentioning
confidence: 99%